Empowering Laikipia County through climate-smart agriculture for peace: A collaborative journey - Kenduiywo, Benson; Belli, Anna; Muruku, Joy (2024)
Science stands at the forefront of addressing the intricate challenges posed by climate change. Through harnessing scientific research and innovation, regions like Laikipia County gain invaluable insights and solutions to aid communities in adapting to and mitigating the adverse impacts of climate change, thereby fostering peace and stability. Consequently, the Alliance of Bioversity and CIAT, in collaboration with the Ministry of Agriculture and Livestock Development, Jomo Kenyatta University of Agriculture and Technology (JKUAT), and the national Climate-Smart Agriculture (CSA) Multi-Stakeholder Platform (CSAMSP), have developed a training course titled "Climate, Peace, and Security in Agriculture Sector" under the CGIAR Initiative on Climate Resilience (ClimBeR). The first pilot training of this course served as a catalyst for collective action and collaboration, paving the way towards building a more resilient and sustainable future for Laikipia County.